Georgia : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
Since the conclusion of the last Article IV Consultation in October 2001, Georgia's macroeconomic performance has been encouraging. The 2003 Article IV Consultation and program discussions were held against the backdrop of protracted deviations from the IMF-supported program. Discussions with government officials and the business community highlighted the need for bolder efforts to improve Georgia's business environment and investment climate.